GENETIC ANALYSIS OF OVER ONE MILLION PEOPLE IDENTIFIES 535 NOVEL LOCI ASSOCIATED WITH BLOOD PRESSURE AND RISK OF CARDIOVASCULAR DISEASE. (June 2018) - Warren, H.R.; Evangelou, E.; Mosen, D.; Mifsud, B.; Pazoki, R.; Gao, H.; Ntritsos, G.; Dimou, N.; Evangelou, M.; Hellwege, J.; Giri, A.; Esko, T.; et al.
Abstract : Objective: Hypertension is the leading cause of cardiovascular morbidity. High blood pressure is highly heritable (∼30–50%), however all genetic variants identified so far only explain ∼3–4% of the trait variance. Hence much of the genetic architecture of blood pressure remains unexplained. Design and method: We report the largest genome-wide association study to date. Our analyses test for association of ∼7 million common genetic variants with systolic & diastolic blood pressure and pulse pressure. Our discovery meta-analyses combine the UK Biobank cohort (N = 458, 577) with the International Consortium for Blood Pressure data (N = 299, 024). Our analysis strategy incorporates both a 1-stage design with internal replication and a 2-stage design with independent replication from the VA Million Veteran Program (N = 220, 520) and the Estonian Biobank (N = 28, 742), totalling over 1 million individuals overall, all of European ancestry. Results: We identify 535 novel loci, replicate 92 loci for the first time, and confirm all 274 published loci. The total 901 blood pressure associated loci more than triples the number of previously known loci. By comparing the upper and lower quintiles of the genetic risk score, the combination of all blood pressure variants is associated with > 10mmHg higher systolic blood pressure and odds of 2.59 and 1.45 for increased risk of hypertension and cardiovascular outcomes, respectively. Pathway analyses show enrichment of pathways targeted by antihypertensive drugs and highlight a novel pathway: transforming growth factor beta (TGFβ), affecting sodium handling in the kidney. Enrichment of blood pressure gene expression is strongest in the vasculature, high in adrenal tissue, and newly observed in adipose tissues. Several novel blood pressure loci (e.g. apolipoprotein-E) are associated with lipids and metabolites, implying pleiotropy across cardio-metabolic traits. We also show genetic overlap between hypertension and lifestyle exposures, with many blood pressure loci also associated with fruit/water/tea/caffeine/alcohol/salt intake, for example. Conclusions: Our novel loci offer new biological insights into blood pressure regulation. The combined effect of all associated variants shows a large aggregated risk, warranting further investigation of a potential precision medicine strategy to prevent future cardiovascular disease amongst patients at high genetic risk.